A Combination of SHA-256 and DES for Visual Data Protection - Aristides Bima Wintaka; Christy Atika Sari; Eko Hari Rachmawanto; Rabei Raad Ali (Jurnal Masyarakat Informatika, 2025)
This study employs SHA-256 and DES algorithms to safeguard visual data through encryption and decryption processes. Research findings demonstrate that this method provides robust security with image histograms that are difficult to recognize and randomly encrypted. The MSE and PSNR values approximate 105 and 48, indicating that the decryption image quality closely resembles the original due to these relatively high values, which are considered excellent. The SSIM value of 1 which indicates no difference in structure, luminance, or contrast between images. Entropy and N.C values approach 8 and 0.92, respectively, suggesting pixel complexity within image with favorable pixel distribution. This technique prove effective for protecting confidential images and digital documents.